1985
DOI: 10.1111/j.1600-065x.1985.tb01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Complexity and Expression of Human Class II Histocompatibility Antigens

Abstract: The genes encoding nearly all of the serologically defined class II antigens of the major histocompatibility complex have been isolated. Three class II loci have been studied in great detail. The DR region contains a single alpha gene and 3 beta chain genes, 1 of which is a pseudogene. The DR alpha chain gene has been linked to a DR beta gene which encodes a beta protein which contains the serological determinant MT3. A second cosmid cluster contains 2 beta genes, 1 of which encodes the DR4 allospecificity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
0
2

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(99 citation statements)
references
References 154 publications
(165 reference statements)
2
95
0
2
Order By: Relevance
“…In search of a shared genetic basis for CVID and IgA-D, we have turned our attention to the major histocompatibility complex (MHC) of genes for two main reasons. First, this region of chromosome 6 encodes a variety of molecules involved in antigen presentation and T-cell/B-cell interactions (15). Second, studies of individuals with IgA-D have revealed a relatively high incidence of certain HLA haplotypes (16,17) and MHC supratypes, the most consistent feature of which is the presence of null alleles of the gene encoding the A isotype of complement component C4 (C4A) (14).…”
Section: Common Variable Immunodeficiency (Cvid) and Selectivementioning
confidence: 99%
“…In search of a shared genetic basis for CVID and IgA-D, we have turned our attention to the major histocompatibility complex (MHC) of genes for two main reasons. First, this region of chromosome 6 encodes a variety of molecules involved in antigen presentation and T-cell/B-cell interactions (15). Second, studies of individuals with IgA-D have revealed a relatively high incidence of certain HLA haplotypes (16,17) and MHC supratypes, the most consistent feature of which is the presence of null alleles of the gene encoding the A isotype of complement component C4 (C4A) (14).…”
Section: Common Variable Immunodeficiency (Cvid) and Selectivementioning
confidence: 99%
“…These molecules interact with antigen peptide fragments and with the T cell receptor [1,2], and their essential role in the immune response together with their great polymorphism explain the association of certain allelic variants with the susceptibility to certain immune disorders [3].…”
Section: Introductionmentioning
confidence: 99%
“…The class II region of the human MHC is at least twice as large as that of the mouse, based on recombination frequency (8) (b) Linkage of a disease to DP would be a special case, since DP genes have little or no linkage disequilibrium with DQ and DR genes. At least one "hot spot" for recombination occurs between DP-DX and DQ-DR (see below).…”
Section: Introductionmentioning
confidence: 99%